2022
DOI: 10.3389/fphar.2022.1017433
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated network pharmacology and metabolomics to reveal the mechanism of QiShenYiQi Dripping Pills against cardiac structural and functional abnormalities

Abstract: Background: Heart failure (HF), the final stage of cardiovascular diseases, is a clinical syndrome of cardiac structural or functional abnormalities. QiShenYiQi Dripping Pills (T101), short for QSYQ (T101), showed effectiveness and safety in the treatment of HF according to modern pharmacological research and clinical studies, but the mechanism remains unclear. This study aims to clarify the mechanism of QSYQ (T101) in treating heart failure through the analysis to critical biomarkers, targets and pathways.Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, recent technological developments in metabolomics, proteomics, genomics, and transcriptomics have provided new insights into the potential use of herbal medicines for disease treatment ( Guo et al, 2022 ). Therefore, interest is increasing regarding the therapeutic applications of traditional Chinese medicine ( Zhang et al, 2022 ; Wu et al, 2022 ; Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent technological developments in metabolomics, proteomics, genomics, and transcriptomics have provided new insights into the potential use of herbal medicines for disease treatment ( Guo et al, 2022 ). Therefore, interest is increasing regarding the therapeutic applications of traditional Chinese medicine ( Zhang et al, 2022 ; Wu et al, 2022 ; Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on modern pharmacological research, Qishen Yiqi dripping pills could adjust vitality and nourish the blood, stimulating pulse, and alleviating pain, which could be used to prevent myocardial injury and enhance the production of myocardial cells (Wu et al, 2023). Clinically, Zhang et al (2022) proved that it mainly treats symptoms of qi deficiency and blood stasis, such as chest tightness and chest pain, shortness of breath, and spontaneous sweating. Chen L, et al (2022) found that Qishen Yiqi dripping pills mainly play an auxiliary role in the treatment of patients with coronary heart disease, and Chen W, et al (2022) demonstrated that Qishen Yiqi dripping pills could be combined with Western medicine to treat diseases such as hypertension and angina.…”
Section: Introductionmentioning
confidence: 99%